2018
DOI: 10.1155/2018/9802475
|View full text |Cite
|
Sign up to set email alerts
|

RK-AES: An Improved Version of AES Using a New Key Generation Process with Random Keys

Abstract: Advanced Encryption Standard (AES) is a standard algorithm for block ciphers for providing security services. A number of variations of this algorithm are available in network security domain. In spite of the strong security features, this algorithm has been recently broken down by the cryptanalysis processes. Therefore, it is required to improve the security strength of this algorithm as AES is popular in commercial use. In this paper, we have shown the reasons of the loopholes in AES and also have provided a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Also, KSA of AES has few nonlinear elements and slower diffusion structure to generate the subkeys. Most of the cryptanalysis attacks on AES takes the advantage of this weakness in its KSA, for example, relatedkey attacks, linear and differential attacks, and combined attack [5,38]. After a little modification, the SAC value of KSA can be improved which can make AES cipher more secure [6,9,13].…”
Section: Bit Independence Testsmentioning
confidence: 99%
“…Also, KSA of AES has few nonlinear elements and slower diffusion structure to generate the subkeys. Most of the cryptanalysis attacks on AES takes the advantage of this weakness in its KSA, for example, relatedkey attacks, linear and differential attacks, and combined attack [5,38]. After a little modification, the SAC value of KSA can be improved which can make AES cipher more secure [6,9,13].…”
Section: Bit Independence Testsmentioning
confidence: 99%
“…It is important to preserve the quality and privacy of these data from the sensors. To preserve the confidentiality of the data to guarantee that it cannot be tampered with, the data can be secured by encrypting the date with the PUF key or mechanisms such as the Message Authentication Code (MAC) and the Advanced Encryption Standard (AES) 256 [135]. The two broad types of application of PUFs are intrinsic and extrinsic [136].…”
Section: Implementation Of Pufsmentioning
confidence: 99%
“…The computed number of pixel change rate and the unified average change intensity revealed that the modified AES is more sensitive to differential attack. Authors in [12] made the various attacks that have been targeted at undermining the strength of AES known. Among these is fault injection attacks that could be used to reveal AES key.…”
Section: Related Workmentioning
confidence: 99%